Isolasi dan Identifikasi Mikroorganisme dari Tempoyak: Produk Fermentasi Tradisional dari Jambi - Setiana Safitri; Ardi Mustakim (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
Tempoyak is a traditional fermented paste made from durian in Indonesia, favored by the Malay ethnic group. While tempoyak holds a unique and significant place in Indonesia's rich culinary diversity, there is a notable gap in research about it compared to other fermented foods such as kimchi. More investigation is essential to grasp the microbial composition, interactions, and possible health advantages of tempoyak, which may offer benefits like boosting the immune system, reducing cholesterol levels, exhibiting probiotic qualities, preservation, and possessing antibacterial effects. Researchers could also discover vital insights regarding the history, cultural significance, production methods, microbiological issues, nutritional aspects, and future prospects of local foods like tempoyak. This research intends to examine and study tempoyak as a traditional fermented food through comprehensive literature review and data from earlier investigations. Tempoyak has a strong connection to Malay cultural identity, regardless of its production location. As a key element of the daily practices of the Malay people in Indonesia, tempoyak is typically featured at cultural events, weddings, or large gatherings. This cultural importance sets Indonesian tempoyak apart from its Malaysian counterpart. The process of making tempoyak involves mashing the durian flesh, mixing in salt, and letting the combined mixture ferment in a sealed container at room temperature for 4 to 7 days. The microbial population in tempoyak can differ but mainly includes Lactobacillus species, particularly Lactobacillus plantarum. Proximate analysis is an effective approach to evaluate the nutritional makeup of tempoyak. Differences in nutrient levels may arise from the various types of durian, salt elements, sterilization periods, temperatures, and length of fermentation. Potential research opportunities could explore tempoyak’s role in fostering sustainable food practices, additional health benefits from its consumption, and the development of innovative products based on tempoyak. The aim of this study will enhance the field and aid in safeguarding and promoting the culinary heritage of the Malay community.